Risk of invasive cervical cancer after atypical glandular cells in cervical screening: nationwide cohort study - Wang, Jiangrong (BMJ, 2016)
Objectives To investigate the risks of invasive cervical cancer after detection of atypical glandular cells (AGC) during cervical screening. Design Nationwide population based cohort study. Setting Cancer and population registries in Sweden. Participants 3 054 328 women living in Sweden at any time between 1 January 1980 and 1 July 2011 who had any record of cervical cytological testing at ages 23-59. Of these, 2 899 968 women had normal cytology results at the first screening record. The first recorded abnormal result was atypical glandular cells (AGC) in 14 625, high grade squamous intraepithelial lesion (HSIL) in 65 633, and low grade squamous intraepithelial lesions (LSIL) in 244 168. Main outcome measures Cumulative incidence of invasive cervical cancer over 15.5 years; proportion of invasive cervical cancer within six months of abnormality (prevalence); crude incidence rates for invasive cervical cancer over 0.5-15.5 years of follow-up; incidence rate ratios compared with women with normal cytology, estimated with Poisson regression adjusted for age and stratified by histopathology of cancer; distribution of clinical assessment within six months after the abnormality. Results The prevalence of cervical cancer was 1.4% for women with AGC, which was lower than for women with HSIL (2.5%) but higher than for women with LSIL (0.2%); adenocarcinoma accounted for 73.2% of the prevalent cases associated with AGC. The incidence rate of invasive cervical cancer after AGC was significantly higher than for women with normal results on cytology for up to 15.5 years and higher than HSIL and LSIL for up to 6.5 years. The incidence rate of adenocarcinoma was 61 times higher than for women with normal results on cytology in the first screening round after AGC, and remained nine times higher for up to 15.5 years. Incidence and prevalence of invasive cervical cancer was highest when AGC was found at ages 30-39. Only 54% of women with AGC underwent histology assessment within six months, much less than after HSIL (86%). Among women with histology assessment within six months, the incidence rate of cervical cancer after AGC was significantly higher than that after HSIL for up to 6.5 years. Conclusions AGC found at cervical screening is associated with a high and persistent risk of cervical cancer for up to 15 years, particularly for cervical adenocarcinoma and women with AGC at age 30-39. Compared with the reduction in risk of cancer seen after HSIL management, management of AGC seems to have been suboptimal in preventing cervical cancer. Research to optimise management is needed, and a more aggressive assessment strategy is warranted.